Nilai Manfaat Ekonomi Hutan Kota Universitas Hasanuddin Makassar - Muthmainnah Zainuddin; Muhammad Tahnur (Jurnal Hutan dan Masyarakat, 2018)
This research aims to (1) identify the current indirect economic benefit resources of Hasanuddin University’s urban forest (2) find out the indirect economic benefit value of Hasanuddin University’s urban forest. This research has been implemented for 6 months during March to August 2018.  The economic benefit value consists of wood value, coolness value and water absorption value.  Method used to obtain the wood value is calculated based on market price approach, the coolness value of the urban forest is based on the market value of substitute goods while the water absorption value is calculated based on the trees’ ability in absorbing water. The research result shows that the urban forest of Hasanuddin University has a very large and high benefit value.  Some indirect economic benefit values contained in the  urban forest are of the wood value, coolness benefit value and water absorption benefit value. The wood value of Hasanuddin University’s urban forest is Rp. 46.586.400/year The coolness economic value is calculated from the total cost of procuring Air Conditioner (AC) and the maintenance cost. The coolness value of Hasanuddin University’s urban forest is Rp. 3.6828.000.000.  The economic value of water absorption of Hasanuddin University’s urban forest is calculated based on the trees’ ability to hold water. The economic value of water absorption of Hasanuddin University’s urban forest is Rp. 384.189,12/days so that the water absorption  of Hasanuddin University’s urban forest is  Rp. 140.229.028,8/year.